An Investigation of Techniques for Teaching Pronunciation in a College-Level Beginner French Course. - Mikkelson, Astri (My University, 2009)
The use of phonetics in teaching French to adult beginning language learners is a controversial technique. This study collected data in a college-level beginner French course over the course of a semester to evaluate the results of pronunciation instruction that employed and that did not employ phonetics.
Color poster with text, images, table, and graphs.
Keywords: Phonetics--Educational aspects; French language--Pronunciation--Study and teaching; Language and languages--Pronunciation--Study and teaching; Posters